2008
DOI: 10.1029/2008gl033511
|View full text |Cite
|
Sign up to set email alerts
|

The case for dynamic subsidence of the U.S. east coast since the Eocene

Abstract: [1] The dynamic subsidence of the United States east coast is addressed using the discrepancy between regional and global estimates of sea level, elevation of paleoshorelines, and adjoint models of mantle convection that assimilate plate motions and seismic tomography. The positions of Eocene and Miocene paleoshorelines are lower than predicted by global sea levels, suggesting at least 50 m, and possibly as much as 200 m of subsidence since the end of the Eocene. Dynamic models predict subsidence of the east c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 21 publications
6
91
1
Order By: Relevance
“…In addition, we also show the recent prediction by Steinberger et al (2015), which is based on a viscosity and density model that is derived from the Grand tomography model ( Steinberger et al, 2015). This prediction is amongst a group of models that predict long-term subsidence of the whole US East coast (Müller et al, 2008;Spasojevic et al, 2008); such models are difficult to reconcile with the observed extent of Pliocene flooding of the ACP since they would require a significantly higher degree of melting during the Pliocene than previously thought (i.e., essentially the disappearance of all ice sheets and glaciers). The total amplitude of the GIA-corrected shoreline elevations is ~50 m and, of the four DT predictions by Rowley et al (2013), the one shown in Figure 7 This localized reversal of the elevation gradient cannot be due to GIA, which produces a relatively smooth signal across the peripheral bulge.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, we also show the recent prediction by Steinberger et al (2015), which is based on a viscosity and density model that is derived from the Grand tomography model ( Steinberger et al, 2015). This prediction is amongst a group of models that predict long-term subsidence of the whole US East coast (Müller et al, 2008;Spasojevic et al, 2008); such models are difficult to reconcile with the observed extent of Pliocene flooding of the ACP since they would require a significantly higher degree of melting during the Pliocene than previously thought (i.e., essentially the disappearance of all ice sheets and glaciers). The total amplitude of the GIA-corrected shoreline elevations is ~50 m and, of the four DT predictions by Rowley et al (2013), the one shown in Figure 7 This localized reversal of the elevation gradient cannot be due to GIA, which produces a relatively smooth signal across the peripheral bulge.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Others have argued that changes in mantle flow-induced dynamic topography (Mitrovica et al, 1989;Gurnis, 1990Gurnis, , 1993Forte et al 1993a,b) have affected the elevation of the ACP (e.g. Müller et al, 2008;Moucha et al, 2008;Spasojević et al, 2008). Most recently, Rowley et al (2013) showed that models of DT change can reproduce the broad North-South tilting trend of the Pliocene shoreline in the ACP, obtaining best fits for the northern part (i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…The earlier period of forward integration is 172 avoided in Model M1, a hybrid model (Spasojevic and Gurnis, 2012), as the initial global 173 mantle temperature field at present-day is estimated through a combination of seismic 174 tomographic inversions of surface and body waves using model S20RTS (Ritsema et al,175 2004) in the lower mantle and one based on Benioff zone seismicity for the upper mantle 176 seismicity. This temperature field is integrated backward using the SBI (simple backward 177 integration) method of Liu and Gurnis (2008) back to the Late Cretaceous by reversing the 178 direction of gravity and plate motions. A hybrid paleo-buoyancy field is generated by 179 merging the backward-advected mantle temperature field with synthetic subducted slabs 180 assimilated into the model based on the location of subduction zones, the age of the 181 subducted lithosphere and relations among subduction zone parameters (Spasojevic and 182 Gurnis, 2012).…”
Section: Geodynamic Models 167mentioning
confidence: 99%
“…Lateral displacements of continents relative to mantle convection patterns have significant impact on the flooding history of continental platforms and margins (Sleep, 1976;Gurnis, 1990Gurnis, , 1993Russell and Gurnis, 1994). Eustatic curves constructed from data from a single margin are known to misrepresent actual global sea levels because of the influence of dynamic topography (Müller et al, 2008b;Spasojević et al, 2008;Moucha et al, 2008). Apart from these continental-scale observations, measurements of the amplitude, wavelength, and rate of dynamic topography resulting from circulation within the convecting mantle are rare.…”
Section: Dynamic Topographic Settingmentioning
confidence: 99%